Forest Proximity Positively Affects Natural Enemy Mediated Control of Fall Armyworm in Southern Africa - Clarkson, Juliet; Borah, Joli R.; Baudron, Frédéric; Sunderland, Terry C. H. (Frontiers in Forests and Global Change, 2022)
The fall armyworm (FAW, Spodoptera frugiperda) is a major crop pest in Africa. It threatens the livelihoods and food security of smallholder farmers in the region by negatively impacting maize yield. Although scientific evidence suggests that natural enemy-mediated predation can potentially reduce FAW infestation, the effectiveness of natural enemies such as birds, bats, parasitoids, and generalist predators on FAW is poorly understood. This study reviews existing literature to assess how birds, bats, parasitoids, and generalist predators’ control FAW infestation, as well as the role of forest or tree cover in natural-enemy mediated pest control of FAW in maize in Southern Africa. We then present a case study to examine the role of forest proximity in reducing FAW infestation in maize in Zimbabwe. We conclude that birds, bats, parasitoids, and generalist predators are likely drivers of the reduced success of FAW near forests in southern Africa. While predators influence FAW survival and development, their role is largely undermined by parasitoids, which are more efficient in affecting FAW populations. Birds, bats, parasitoids, and generalist predators play an important role in controlling FAW on farms on heterogenous landscapes with diverse vegetation and near-forest proximity. The findings of our case study from Zimbabwe suggest that the distance to forest had a much higher impact on FAW incidence than maize variety, planting date, or the rate of nitrogen applied. Lack of enough case studies from maize in southern Africa makes it challenging to assess the mechanism and the effectiveness of bird predation on FAW. For this reason, further research is necessary to examine how predation by birds, bats and arthropods and parasitism impacts maize yield. We discuss research barriers, recommend appropriate methods for experimental studies, and suggest possible management options to control FAW in southern Africa.